Is Psychopathy a Dynamic Risk Factor? An Empirical Investigation of Changes in Psychopathic Personality Traits Over the Course of Correctional Treatment - Moosburner, Maeve (Criminal justice and behavior, 2024)
This study examined whether there would be significant group-level and reliable individual changes in psychopathy measured via the Psychopathy Checklist–Revised (PCL–R) and the Interpersonal Measure of Psychopathy (IM–P) scores in a sample of 187 adult individuals with violent and sexual offense histories incarcerated and treated in a German social therapy facility (STF). Measurements were taken at entry into the STF and at (most) an 18-month follow-up. The results of dependent t-tests were significant, showing significant reductions in PCL–R and IM–P scores. Stronger significant reductions were observed for PCL–R Factor 1 scores and its corresponding facets compared with Factor 2 scores. Reliable individual changes measured via the Reliable Change Index (RCI) showed improvements in PCL–R and IM–P scores for some participants.